Learning GitHub : setting up and managing repositories for sharing and collaboration - Porteneuve, Christophe (O'Reilly, 2015)
"In this Learning GitHub training course, expert author Christophe Porteneuve will teach you how to set up and manage repositories for sharing and collaboration in GitHub. This course is designed for the absolute beginner, meaning no experience with GitHub is required. You will start by learning about the GitHub workflow, including how to create and manage branches and pull requests. From there, Christophe will take you beyond the site, teaching you how to use the Cli and desktop apps. This video tutorial also covers how to search GitHub, manage issues and fixes, and take security precautions. You will also learn about repository management, including key terms, switching visibility, and collaborators and permission levels. Finally, you will learn how to be social and collaborative, including how to watch repositories and follow people, choose licenses, and write a great README. Once you have completed this computer based training course, you will have learned how to implement the GitHub workflow, manage issues and pull requests efficiently, secure your GitHub account, and optimize collaboration."--Resource description page.